2011
DOI: 10.1590/s1517-83822011000100026
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quinolone-resistance mutations in Salmonella spp. strains of epidemic and poultry origin

Abstract: Mutations into codons Aspartate-87 (62%) and Serine-83 (38%) in QRDR of gyrA were identified in 105 Salmonella strains resistant to nalidixic acid (94 epidemic and 11 of poultry origin). The results show a high incidence of mutations associated to quinolone resistance but suggest association with others mechanisms of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The presence of the main serotype, S. enteritidis in poultry was also confirmed by other researchers in various regions of Brazil, such as Paraná (Souza et al, 2011), São Paulo (Hofer et al, 1998;Lima et al, 2009), Bahia, Ceará, Goiás, Paraná, Mato Grosso, Mato Grosso do Sul e Santa Catarina (Kanashiro et al, 2005), Rio Grande do Sul (Ribeiro et al, 2007) and the other states in the Northeast (Duarte et al, 2009). Similarly, in other countries, the occurrence of S. enteritidis isolated from broilers in Portugal (Antunes et al, 2003), Spain (Fernandez -Rubio et al, 2009) Lithuania (Ruzauskas et al, 2005) and United States (Burkholder et al, 2008) was observed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The presence of the main serotype, S. enteritidis in poultry was also confirmed by other researchers in various regions of Brazil, such as Paraná (Souza et al, 2011), São Paulo (Hofer et al, 1998;Lima et al, 2009), Bahia, Ceará, Goiás, Paraná, Mato Grosso, Mato Grosso do Sul e Santa Catarina (Kanashiro et al, 2005), Rio Grande do Sul (Ribeiro et al, 2007) and the other states in the Northeast (Duarte et al, 2009). Similarly, in other countries, the occurrence of S. enteritidis isolated from broilers in Portugal (Antunes et al, 2003), Spain (Fernandez -Rubio et al, 2009) Lithuania (Ruzauskas et al, 2005) and United States (Burkholder et al, 2008) was observed.…”
Section: Discussionsupporting
confidence: 79%
“…The serotypes isolated from broiler litter were found by Andreatti who reported S. enteritidis, S. infants and S. kentuky present in broiler litter in the state of São Paulo, Brazil, and also Souza et al (2011) who researched the resistance profile of quinolones against strains of Salmonella isolated from poultry farms in Paraná and found out that out of the 123 isolates, 90 belonged to S. enteritidis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results in this study nearly in coordinated with Reyna et al, (1995) who stated that double and triple combinatorial mutations involving residues 83 and 87 of gyrA are associated with much higher resistance levels than those of single mutations and Hirose et al, (2002) who reported a single mutation in the gyrA gene, at either position 83 or 87 of gyrA in Salmonella enterica Serovar Typhi and Serovar Paratyphi A and double mutations in the gyrA gene at both position 83 and position 87 of gyrA in strains with highlevel resistance to Fluoroquinolones induced by in vitro selection with ciprofloxacin. The mutations (Ser83Phe and/or Asp87Gly) were previously recorded in many reference Salmonella strains and also in strains isolated from food and domestic or wild birds as reported by (Reyna et al, 1995;Hirose et al, 2002 andDe Souza et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…2 Ciprofloxacin is synthetic antimicrobial agent commonly prescribed against enteric fever belongs to second generation 4-quinolones which is also known as fluoroquinolones and acts by inhibiting bacterial Topoisomerase II (DNA gyrase) which is required for DNA supercoiling and Topoisomerase IV which is required for strand separation during cell division. 3 The wide spread use of ciprofloxacin in recent years (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), several treatment failures have also been reported due to decreased susceptibility of ciprofloxacin. 4,5 Generally, a single mutation (Ser-83 to Phe or Ser-83 to Tyr) in gyr A was associated with reduced susceptibility to ciprofloxacin (MIC 0.125-1 mg/L) and nalidixic acid resistant.…”
Section: Introductionmentioning
confidence: 99%